2010 International Conference on Field-Programmable Technology 2010
DOI: 10.1109/fpt.2010.5681538
|View full text |Cite
|
Sign up to set email alerts
|

Parallelizing FPGA placement using Transactional Memory

Abstract: Abstract-To capitalize on the growing abundance of multicore hardware, FPGA vendors have begun to parallelize the most compute intensive algorithms in their CAD software. However, parallelization is a painstaking and hence expensive process that limits the number of algorithms that can be cost-effectively parallelized. Transactional Memory (TM) promises an easier-touse alternative to locks for critical sections in threaded codeallowing programmers to avoid deadlocks and data races, and also allowing critical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Generally speaking, larger circuits have better performance than smaller ones. This is consistent with the observation from TVPR that parallel moves for large circuits are less likely to conflict [7].…”
Section: ) Movespec-htmsupporting
confidence: 81%
See 4 more Smart Citations
“…Generally speaking, larger circuits have better performance than smaller ones. This is consistent with the observation from TVPR that parallel moves for large circuits are less likely to conflict [7].…”
Section: ) Movespec-htmsupporting
confidence: 81%
“…Automatic tracking by the hardware provides two major advantages: tracking instructions become unnecessary and the programmer only needs to annotate transaction boundaries; and the overhead associated with tracking becomes minimal. The authors of TVPR observed that TVPR should attain much higher speedups using HTM [7]. However, unlike STM, hardware has limited capacity and hence the amount of data that can be tracked by any HTM system is limited.…”
Section: Transactional Memorymentioning
confidence: 99%
See 3 more Smart Citations